HUBUNGAN KREDIT DAN SUKU BUNGA DENGAN INFLASI DI INDONESIA - Azka Rizkina; Cut Zakia Rizki (Syiah Kuala University, 2017)
This study is aimed to see the relationship of causal credits consumption, investment credit and interest rates with inflation in Indonesia. The analysis model used in this research is VAR / VECM model using monthly data from 2005: 01 until 2015: 12. The results showed that by using granger causality test, there was a two-way causal relationship between Bi Rate and inflation. There is a one-way causality relationship between inflation and investment credit. However, consumption credit has no causality relationship with inflation. Because consumer credit is a requirement that must be fulfilled so that public does not pay attention to the effect of price increase (inflation). Bank Indonesia will maintain the stability of inflation by lowering the BI Rate, so that people take credit that will improve the consumption and increase the investment so that the increasement in economic is growth steadily. Further research is expected to be able to add variable working capital credit to see the comparison of credit growth according to its usefulness.